2015
DOI: 10.1007/s11255-015-1089-7
|View full text |Cite
|
Sign up to set email alerts
|

Longer duration of catheter patency, but similar infection rates with internal jugular vein versus iliac vein tunneled cuffed hemodialysis catheters: a single-center retrospective analysis

Abstract: Taken together, our results suggested that iliac vein TCCs present an increased risk of dysfunction compared to internal jugular vein TCCs in elderly hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…If patients have contraindications to anticoagulants (thrombus greater than 6 cm or abnormalities of the heart), thrombectomy can be considered. 9,10 Although the effort to make AV fistulas in hemodialysis patients increase, the prevalence of tunneled hemodialysis catheters remains high (National Vascular Access Initiative, Fistula First). In the United States, the use of TDC was 62.3% in hemodialysis patients in 2006.…”
Section: Discussionmentioning
confidence: 99%
“…If patients have contraindications to anticoagulants (thrombus greater than 6 cm or abnormalities of the heart), thrombectomy can be considered. 9,10 Although the effort to make AV fistulas in hemodialysis patients increase, the prevalence of tunneled hemodialysis catheters remains high (National Vascular Access Initiative, Fistula First). In the United States, the use of TDC was 62.3% in hemodialysis patients in 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, accidental injury may occur to the peritoneal sac, thus leading to peritonitis. Furthermore, compared to internal jugular vein, there is an increased risk of catheter dysfunction, while infectious complications seem to be similar [3]. Malposition of a dialysis catheter introduced via the femoral vein into the ALV has been described [4,5], but a similar situation is not reported for cuffed tunneled catheters placed into the iliac vein.…”
Section: Discussionmentioning
confidence: 99%
“…These conditions are thought to contribute to formation of fibrin plaques on the wall of the vein. 24 Moreover, in a clinical study, we found that the TCC dysfunction rate was higher in the iliac vein than in the internal jugular vein, 48 which suggests that different directions of blood flow may also influence formation of a fibrin sheath and thrombosis, but this awaits further investigation.…”
Section: Fibrin Sheathmentioning
confidence: 92%